Experimental Study on Performance of Semiconductor Cooling Device for Communication Cabinet Cooling - Yang Wansheng; Chen Shilin; Bi Yin (Zhileng xuebao, 2017)
In this study, a cabinet semiconductor cooling device was designed and its refrigerating capacity and cooling efficiency were tested using a test platform. The performance parameters were obtained according to test-based analyses of the refrigerating capacity, cooling efficiency, and other factors. According to the test results, for an average indoor temperature of 26 ℃ and 200-360 W input power, the cooling efficiency first increases and then decreases, reaching a maximum value of 69.5% when the input power is 232 W. Meanwhile, the average amount of refrigeration throughout the test is 455.46 kJ and the power of the semiconductor cooling device is 151.8 W, which can remove 3.04% of the energy in a 5 kW communication cabinet.